Screening for pulmonary veno-occlusive disease in heterozygous EIF2AK4 variant carriers. Issue 2 (18th August 2022) - Lechartier, Benoit; Girerd, Barbara; Eyries, Mélanie; Beurnier, Antoine; Humbert, Marc; Montani, David
Pulmonary veno-occlusive disease (PVOD) is a rare form of pulmonary arterial hypertension (PAH), characterised by a specific phenotype and associated with a poor prognosis, often justifying an early referral for lung transplantation [1–4]. The pathological hallmark of PVOD is a preferential involvement of the pulmonary venous system with the obliteration of small pulmonary veins by fibrous intimal thickening and patchy capillary proliferation [5]. Comprehensive evaluation as well as longitudinal follow-up of a cohort of EIF2AK4 heterozygous variant carriers did not raise any suspicion of pulmonary veno-occlusive disease (PVOD), confirming the recessive inheritance of EIF2AK4 -linked PVOD https://bit.ly/3H8wPVR